APLIKASI SIMULASI 3 DIMENSI BANGUN RUANG UNTUK SEKOLAH DASAR (SD) BERBASIS ANDROID - Hotmian Sitohang; Muliawardi Astrianingsih (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
Along with the development of computer and information technology, has been a lot of changes in viewpoint and way of learning someone. Students now are more looking at something based on the function and attractiveness in the learning process.Along with the development of computer and information technology, has been a lot of changes in viewpoint and way of learning someone. Students now are more looking at something based on the function and attractiveness in the learning process. Learning Mathematics in the material geometry taught in the sixth grade students in elementary school (SD) still use the model of learning by drawing on paper manila by following the pattern geometry such as balls, slinder, cone, pyramid, cubes, blocks and prisms. This makes many students feel bored and wasting time because the students are now proficient in using mobile technology. So, we need a learning simulation that can help learning in order to create interesting and fun learning environment for elementary school students as well as additional teaching aids for teachers. This research aims to create a 3D space simulation wake of learning that can be implemented in mathematics so that it appears interest in students and help students to learn everyday. Because this application is also equipped with the question and the way it's done.The results of this penlitian is a simulation applications of 3D geometry-based android as a learning tool for elementary school students that contains all kinds of geometry, materials, formulas, and sample problems and how to solve problems that can help students to be easy to learn geometry.